Fibrosis progression in maintenance liver transplant patients with hepatitis C recurrence: a randomised study of everolimus vs. calcineurin inhibitors. (15th December 2013) - Villamil, Federico G.; Gadano, Adrian C.; Zingale, Fernanda; Perez, Roberto; Gil, Octavio; Yantorno, Silvina; Mastai, Ricardo; Cairo, Fernando O.; Otero, Alcira B.; Dong, Gaohong; Lopez, Patricia; the REVERT Study Group
Abstract Background & Aims Robust clinical data evaluating fibrosis progression in hepatitis C virus (HCV) liver transplant patients receiving an mTOR inhibitor vs. calcineurin inhibitor (CNI) are lacking. To evaluate fibrosis progression in maintenance liver transplant patients receiving everolimus‐ or CNI‐based immunosuppression. Methods In a randomised, multicentre, open‐label study, 43 maintenance liver transplant patients with recurrent HCV infection were randomised to continue CNI‐based immunosuppression or switch to everolimus. Results For patients with biopsy data at month 12, mean Ishak–Knodell fibrosis score at baseline was 2.6 ± 0.9 (n = 14) with everolimus vs. 1.9 ± 1.1 (n = 18) with CNI (P = 0.043), and 1.9 ± 1.2 vs. 2.2 ± 1.3 at month 12. Ishak–Knodell fibrosis score decreased from baseline to month 12 by a mean of −0.7 ± 1.1 with everolimus, but increased by 0.2 ± 1.2 with CNI (P = 0.046). No acute rejection or graft losses occurred up to month 12. Estimated GFR at month 12 was 65.6 ml/min/1.73 m2 with everolimus and 62.2 ml/min/1.73 m2 with CNI [mean difference 3.4 ml/min/1.73 m2 compared to CNI control group, 95% CI −4.9, 11.8 ml/min/1.73 m2, P = 0.411 (analysis of covariance adjusting for baseline GFR)]. Adverse events occurred in 95.5% of everolimus patients and 71.4% of CNI patients (serious adverse events 31.8% and 0.0%, respectively). Adverse events led to everolimus discontinuation in five patients (22.7%). Conclusions This exploratory study suggests that conversion from CNI to everolimus reduces progression of liver fibrosis, and preserves renal function without jeopardising efficacy in liver transplant recipients with recurrent HCV, but is associated with a higher incidence of adverse events and serious adverse events. These preliminary findings merit examination in a larger trial.